Valores e circunstâncias do pensamento geográfico francês (parte dois) : a “Nouvelle Géographie” segundo o testemunho de Joël Charre - Dante F. C. Reis Junior (Confins)
Motivated by the objective of gathering and comparing versions about the meanings and implications of the methodological turn in Geography, between the 1960s and 1970s, we present here a sample of testimonies collected from three important protagonists of scientific change in France. We understand that the value of these personal representations about the events of that time lies in the fact that, although they result from singular experiences and possible idiosyncrasies, because they derive from a posteriori reflexive appreciation (already distanced from that period), they are very useful both to demonstrate the general characters of the paradigm shift (by the possible confluence of their impressions), and to attest the inherent ambiguities (by virtual dissent). In this second part, we present the testimony of Joël Charre, which was very enlightening. And for a specific reason: since he had a partnership with Chamussy and Brunet (for a while and in particular conjunctures), this character gives us a narrative that corroborates certain interpretations about the movement, but also makes possible to highlight some discrepancy of impressions about it.